The relationship between vegetation and soil moisture reveals the vegetation carrying capacity threshold—A case study of a Haloxylon ammodendron plantation in the Alxa desert, China - Zhou, Dongmeng; Si, Jianhua; He, Xiaohui; Jia, Bing; Zhao, Chunyan; Wang, Chunlin; Qin, Jie; Zhu, Xinglin; Liu, Zijin (Frontiers in Environmental Science, 2023)
Afforestation is an important and effective way to curb wind-sand hazards in the Alxa Desert. However, over-afforestation makes soil drying occur frequently. The formation of a soil drying layer seriously restricting the effectiveness of vegetation construction and regional ecological stability. To clarify the process of soil desiccation in Haloxylon ammodendron plantations and determine the suitable planting years, a typical H. ammodendron plantation in this area was selected as the research object, and the soil moisture variation characteristics of this sand-fixing vegetation region with vegetation age were analyzed. The results showed that the H. ammodendron plantation after 11 years of forest growth, the pattern of soil moisture changed, and the soil moisture in the deep layer decreased with increasing vegetation age. After the establishment of sand-fixing vegetation for 30 years, the soil moisture in the deep layer was only 1–3%. Based on the analysis of the soil water supply, consumption and water balance of H. ammodendron plantations, the soil water storage of the 0–400-cm soil layer in different forest ages was significantly different, and the soil water storage of 5–11-year-old forests was the highest. The soil water supply was greater than soil water consumption, and the soil water storage in the profile increased with the increase in precipitation, while the H. ammodendron plantation after 22 years of age soil water consumption was greater than soil water supplementation, and the soil water of the H. ammodendron plantation continuously appeared to be negatively balanced. Therefore, to prevent the soil water ecological environment of H. ammodendron plantations from further deterioration, it is suggested that the growth period of H. ammodendron plantations should not exceed 22 years. The results of this study can provide a scientific basis for afforestation and soil dry layer regulation in the Alxa Desert area.